Conscience as a historical force - Harvey, Douglas S., author.
1 online resource.
Keywords: "Conscience as a Historical Force is the first true analysis of the life and thought of the radically democratic eighteenth-century backcountry figure of Herman Husband (1724-1795) and his heavily metaphorical political and religious writings during the "Age of Revolution." With a chronological approach, this study is of great use to students and scholars interested in the politics and religion of eighteenth-century America"--